Effect of 2 referral intervals on diagnostic discordance between cytology and histology at a colposcopy clinic. Issue 3 (23rd January 2013) - Saayman, Francois; Van Gelderen, Cyril J.; Michelow, Pam; Van Den Berg, Eunice J.; Adam, Yasmin
Abstract: Objective: To determine the effect of the time interval between cervical cytology screening and histology at treatment on grade of cervical disease. Methods: In a retrospective cross‐sectional study at a colposcopy clinic in Soweto, Johannesburg, South Africa, data were compared from women with cytologic abnormalities referred for colposcopy between April 2003 and June 2010 to determine whether early (≤ 180 days) or late (> 180 days) referral had an impact on dysplasia grade. Results: In the early and late referral groups, there were 213 (13.43%) and 201 (14.63%) women, respectively, with upgrading of cervical dysplasia ( P = 0.35), and 1373 (86.57%) and 1173 (85.37%) women, respectively, with downgrading or no change ( P = 0.35). Risk factors for upgrading were HIV infection (odds ratio [OR], 1.63; P < 0.001) and condom use (OR, 1.30; P = 0.02). Four cases (0.68%) of invasion among women with low‐grade squamous intraepithelial lesion (LSIL) and 50 cases (2.11%) among women with high‐grade SIL (HSIL) were not detected by cytology. Risk factors for invasive disease on histology were age (OR, 1.09 per year; P < 0.001), parity (OR, 1.32 per pregnancy; P < 0.001), and HSIL on cytology (OR, 3.17; P = 0.03). Conclusion: There was no difference in the up‐ or downgrading of cervical dysplasia between the 2 referral groups.